Temporal Resource (Dis)continuity for Conservation Biological Control: From Field to Landscape Scales - Iuliano, Benjamin; Gratton, Claudio (Frontiers in Sustainable Food Systems, 2020)
Conservation biological control (CBC) seeks to promote the occurrence of natural enemies of agricultural pests by managing habitat to provide key resources in and around farm fields. In particular, vegetation diversity may help ensure temporal resource continuity such that natural enemies are less likely to experience detrimental gaps or bottlenecks as they move through and use different habitats. While the conceptual value of resource continuity has long been recognized by CBC researchers and practitioners, empirical studies have tended to focus on snapshots in space and time. Here we review how continuity of trophic (food) and structural (shelter) resources affect natural enemy conservation and pest control outcomes within farm fields and across agricultural landscapes. Key trophic resources include alternative prey and non-prey food (such as floral nectar and pollen), which can bolster natural enemy nutrition when pests are scarce. Vegetative and non-vegetative structural resources can protect enemies when crop fields are disturbed and provide important overwintering habitat in temperate regions. Within fields, non-crop plantings such as wildflower strips or beetle banks are the most popular habitat management strategies, but temporal intercropping, asynchronous planting/harvesting, and the construction of artificial shelters have high potential to contribute to resource continuity. Analogously, semi-natural habitat at the landscape scale may contribute to resource continuity in some cases, but crop diversity, asynchrony, and urban habitat can also be important. Simultaneous consideration of resource diversity and continuity could generate better predictions and more targeted management interventions for particular pest and enemy assemblages. Future research should strive to expand our understanding of natural enemy resource requirements in space and time.